Condições ambientais e características de potabilidade da água de bicas de uso público da cidade de Taubaté- SP - de Faria, Ana Lucia; Lacava, Pedro Magalhães; Araújo, Ana Júlia Urias dos Santos; dos Santos, Sandra Irene Sprogis; Vilella, Fátima Regina de Moura Abreu (Revista Biociências, 2008)
Subterranean waters are bodies of water which may emerge to the surface by means of water wellsprings and springlets, they are commonly utilised by man for several activities. The objective of this study was to evaluate the standard of water potability of 12 springlets of public use and human consumption in the city of Taubaté-SP. The parameters used for evaluation were: bacteriological-total coliforms reckoning and Escherichia coli; physical-chemical- cloudiness and nitrate concentration; parasitological-presence of Cryptosporidium spp and Giardia spp. The water samples were collected according to the established methodology by Standard Methods for the Examination of Water and Wastewater (APHA, 1998), in three different stages in the year of 2005. The analyses results in consonance with the Decree number 518/2004, of Health Ministry, revealed that, from 36 samples of analyzed water were considered drinkable: 67% as for the bacteriological standard, 92% as for the physical-chemical standard; and 100% as for the parasitological standard. Considering the whole analyzed parameters in three collections, it was concluded that 58% of springlet water samples studied were considered drinkable. We point out that, during the study it was not identified any type of water quality monitoring in the studied springlets, what may put the population health at risk.